Piracy on the high sands: covert military mobilities in the Libyan desert, 1940-1943 - Forsyth, Isla (Elsevier, 2017)
This paper explores the history of the Long Range Desert Group (LRDG) who gained notoriety in the Second World War by conducting a new form of covert warfare deep behind enemy lines. The LRDG waged a psychological war; continuously appearing and disappearing, they succeeded in creating a sense that the British were everywhere and yet nowhere. In order to effectively execute these covert operations LRDG soldiers became closely acquainted with the desert, their senses attuned to a battlefield of sand, wind and stars. This paper is a study of military bodies and technologies adapting to perform a novel form of deceptive warfare. Examined from the British military’s perspective it explores how the desert-modified car mingled biology, technology and environment to produce a new form of military mobility which shaped the character and legitimised the use of covert desert warfare. It also reveals how covert warfare was naturalised through a heroic narrative of piracy which inspired the group’s inception, justified its establishment and methods, and framed the soldiers’ own performance and understanding of their actions. Overall, the paper uses mobilities research to expose the processes which legitimise warfare strategies. It also argues that it is only by examining these mobilities that such narratives can be held accountable.